Aggressiveness-guided nodule management for lung cancer screening in Europe: justification for follow-up intervals and definition of growth - Prokop, Mathias; Schaefer-Prokop, Cornelia; Jacobs, Colin; Snoeckx, Annemiek; Biederer, Jürgen; Frauenfelder, Thomas; Gleeson, Fergus; Kauczor, Hans-Ulrich; Parkar, Anagha P.; Vliegenthart, Rozemarijn; Revel, Marie-Pierre; Silva, Mario; et al. (European radiology, 2025)
The European Society of Thoracic Imaging (ESTI) nodule management recommendation for lung cancer screening with low-dose CT builds on existing nodule management guidelines but puts a stronger focus on lesion aggressiveness and measurement error. Key objectives included finding a compromise between the overall number of follow-up examinations, avoiding a major stage shift, and reducing the risk for overtreatment. Nodule management categories at baseline are chosen depending on the size of a solid nodule or the solid component of a subsolid or cystic nodule, with suspicious morphology upgrading risk to the next higher category. Higher risk categories mandate shorter follow-up times or diagnostic workup. Volume is the preferred size measure, with diameter measurements as a fallback if segmentation for volumetry is inaccurate at visual control. Nodule aggressiveness at follow-up is estimated from growth rate, calculated as volume doubling time (VDT), or yearly diameter change. Calculation of growth rate, however, is strongly affected by measurement variability, with large error margins for short follow-up and slower growing lesions. Growth thresholds were therefore set so that rapidly growing lesions can be identified while still small, while unnecessary workups for benign or slow-growing lesions could be kept low. New lesions that are retrospectively visible on earlier scans are managed according to their growth rate. New nodules not visible on earlier scans are followed after 3 months if they have a volume of ≥ 30 mm3.
Veröffentlicht: 01. Juli 2025
Gesehen am 06.11.2025